Therapeutic Communication in Elderly Patients: A Systematic Literature Review - Nurhidayah Amir; Neng Ratih Widiyastuti; Fathia Fakhri Inayatu Said; Rifki Sakinah Nompo (HM Publisher, 2023)
The aging process can cause changes in physical, cognitive, and social aspects. Some seniors may experience memory problems, speech difficulties, or hearing difficulties. These factors can affect their ability to communicate effectively, especially in a medical environment that is often complex and full of technical terms. In addition to physical challenges, older adults may also face feelings of loneliness, social isolation, or feelings of being unappreciated. This study aimed to explore the principles and strategies of effective therapeutic communication in interacting with the elderly. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding therapeutic communication in the elderly. This study follows the preferred reporting items for systematic reviews and meta-Analysis (PRISMA) recommendations. Therapeutic communication with the elderly is a communication approach that is empathetic, caring, respects patient autonomy, and uses language that is simple, clear, and easy to understand. Honesty and openness in conveying information about health conditions and prognosis are also important. Avoid giving false hope, but keep focusing on efforts and steps that can be taken to improve the quality of life for the elderly.